Minimizing the Shipping Costs for Soes Cakes by Sari Asih SME Using the Transportation Method - Aprilia, Hafiza; Dewi, Sarastya; Hamidah, Siti Nur (Universitas Insan Cendekia Mandiri, 2025)
The increasing demand for jobs in Indonesia, coupled with limited employment opportunities, has encouraged many to establish Small and Medium Enterprises (SMEs). Effective management is vital, especially for businesses with multiple branches, to ensure efficient product distribution and cost minimization. This study focuses on Sari Asih SME, a soes cake producer with several production facilities that supply various marketing locations. Using the Transportation Method from operational research, the study found that the optimal shipping cost is IDR 48,750, demonstrating a feasible and efficient solution.